Parental support and diversity in sibling personality - William Foley; Lea Katharina Kröger; Jonas Radl (Advances in Life Course Research, 2025)
Personality is associated with important life outcomes such as occupational status, and there is continued interest in understanding how family processes shape people's character. Previous research has shown that despite being exposed to a common family environment, sibling personalities differ substantially. We test one explanation of this phenomenon: differential parental support within families. Fitting family fixed-effects models to data from the German Socio-economic Panel (SOEP), we find that, even within families, differences in parental support contribute to explain the personality of adolescent children. However, this association declines when children reach early adulthood. We interpret these results as demonstrating the importance of within-family factors for shaping personality, and how the influence of parent-child relationships varies over the life course.
Keywords: 300; Personality; Adolescence; Early adulthood; Siblings; Parents; Fixed-effects